2011
DOI: 10.5114/pwki.2011.24739
|View full text |Cite
|
Sign up to set email alerts
|

Special article Magnetocardiography in clinical cardiology. Status quo and future applications

Abstract: 215Magnetocardiography in clinical cardiology. Status quo and future applications Magnetokardiografia w kardiologii klinicznej. Stan obecny i przyszłe zastosowania B Bo or ri is s L Le ei it th hä äu us se er r 1 1 , , F Fr ri ie ed dr ri ic ch h J Ju un ng g 2 2 , , J Ja ai i--W Wu un n P Pa ar rk k Special article/Artykuł specjalny A b s t r a c tMagnetocardiography (MCG) is a non-contact, non-invasive technique for the assessment of electromagnetic activity of the human heart. Theoretical considerations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…Thus, electromyography (EMG) and mechano or vibro or acceleromyography (usually named MMG) are examples of well-established methods that are widely used today in basic, sports and clinical studies. However, another physical quantity, magnetic fields associated with the flux of ions across the active cells membranes, has been well reported in organs such as brain (Hari and Salmelin, 1997 , 2012 ; Nevalainen et al, 2014 ) and heart (Geselowitz, 1979 ; Fenici et al, 2005 ; Leithäuser et al, 2011 ) although much less frequently for the skeletal muscles. Interestingly, though, few previous authors have pointed out that the recording of magnetic fields of this tissue may help to improve our knowledge in respect of its physiology under normal and pathological conditions.…”
mentioning
confidence: 99%
“…Thus, electromyography (EMG) and mechano or vibro or acceleromyography (usually named MMG) are examples of well-established methods that are widely used today in basic, sports and clinical studies. However, another physical quantity, magnetic fields associated with the flux of ions across the active cells membranes, has been well reported in organs such as brain (Hari and Salmelin, 1997 , 2012 ; Nevalainen et al, 2014 ) and heart (Geselowitz, 1979 ; Fenici et al, 2005 ; Leithäuser et al, 2011 ) although much less frequently for the skeletal muscles. Interestingly, though, few previous authors have pointed out that the recording of magnetic fields of this tissue may help to improve our knowledge in respect of its physiology under normal and pathological conditions.…”
mentioning
confidence: 99%
“…[4][5][6] The controlled use of the magnetic field proved beneficial in the therapeutic domain through animal research. 6,7 The electrical activity of the excitable cells such as a neuron, 8 muscles, 9 creates an inherent magnetic field and this bioelectric stimulation plays a role in muscle and different organ functions in a human. 10 Literature also states that a static magnetic field stimulates bone formation via osteoblastic differentiation or activation.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetocardiography (MCG) involves capturing magnetic field maps (MFM's) of current distributions resulting from cardiac action potentials [6][7][8][9][10][11][12][13][14]. It has been shown that MCG gives significant improvements in diagnostic capability over an ECG [15][16][17][18][19][20][21][22][23][24][25][26]. Significantly, in this respect, it has been demonstrated that MCG is capable of reliable detection of non-STelevated myocardial infarction (NSTEMI) [15,22], which are by definition difficult to detect using ECG.…”
Section: Introductionmentioning
confidence: 99%